Relevance of scoring systems in acute appendicitis - Tandi, Niranjan S.; Pai, Srinivas; Mulla, Sameer Ahmed; Kini, Aakarsh G. (International Surgery Journal, 2019)
Background: Acute appendicitis continues to be a clinical dilemma, despite the addition of myriad diagnostic modalities to the surgeon’s arsenal. A reliable scoring system would help streamline diagnosis as well as avoid unnecessary surgeries, in a limited resource setting. Methods: Retrospective observational study evaluating 2 clinical scoring systems for acute appendicitis. Results: For Teicher and Izbicki scores, a sensitivity of 49.5% and 55.71%, specificity of 63.41% and 51.22%, positive predictive value of 92.22% and 90.90%, negative predictive value of 12.56% and 11.67%, negative appendicectomy rate of 8.82% and 10% were found respectively. Conclusions: Acute appendicitis is one of the most common cases presenting to the general surgeon and its diagnosis continues to be clinical enigma, owing to a variety of presentations, degrees of severity and differential diagnoses. Our study shows that Teicher and Izbicki scoring systems can be of value in decision making in acute appendicitis and in reducing the number of negative laparotomies, particularly in limited resource settings where access to advanced diagnostic modalities is limited and expensive. Amongst the two scoring systems, the Teicher score appears to be superior in reducing the negative appendicectomy rate.